2m-4m=6

Simple and best practice solution for 2m-4m=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m-4m=6 equation:


Simplifying
2m + -4m = 6

Combine like terms: 2m + -4m = -2m
-2m = 6

Solving
-2m = 6

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '-2'.
m = -3

Simplifying
m = -3

See similar equations:

| x+31=14 | | 8x-15x-30x-51x=53x+31x-72 | | 6x+15y=2000000 | | Y=12-2(0) | | 6x=9+8 | | 8x-2x-2=1 | | 3(c+7)-6c=4 | | 4cos(2x-60)=2 | | 24x^2+3x-2=0 | | 2x+10-6x= | | 2a^2-pa+3=0 | | 7x(1-5)+2=6 | | 4x-6=-3x | | D+7=3d-2 | | 18-9+r^2=0 | | 8+6x=11x+12 | | log(51x)+log(2x)=log(3x)+log(1) | | (14x^2+7x)9x^2= | | 4q=12-2q | | 15x-7=5(3x-1) | | 10x-5=-6x-7 | | ln(4x)+2ln(x)=ln(3x)+ln(1) | | 3(1.25-2.48x)=8.15x+5.86 | | x+4y-z=-4 | | 8x-y+4z=46 | | 1.59x+3.01=10.9x+1.29 | | 4(x-5)=4s-20 | | 1.50x+5=8.25 | | 2u+4(u-3)=30 | | -8+2x-9+3x-10=21 | | .50x+5=8.25 | | 12p+3q= |

Equations solver categories